Development of Web-Based Interactive Learning Media Using the Learning Management System in the Artificial Intelligence Course, Faculty of Engineering - Khofifah Al Mukarramah; Udin Sidik Sidin; Sanatang Sanatang (Jurnal Pendidikan Terapan, 2026)
This study aims to analyze the level of validity, practicality, and effectiveness of the development of web-based learning media in the Artificial Intelligence course at the Department of Electrical Engineering, Faculty of Engineering, State University of Makassar. The research uses the Research and Development (R&D) method with a mixed methods approach. Media development integrates ADDIE, 4D, and Borg and Gall models which include the analysis, design, development, implementation, evaluation, and dissemination stages. The research design used the Nonequivalent Pretest and Posttest Control Group Design. The research subjects consist of 42 validators of material experts, validators of media experts, and 42 students of Electrical Engineering Education class of 2024 and 298 students of Informatics and Computer Engineering Education class of 2024. Data collection techniques were carried out through observation, interviews, questionnaires, and experiments, while data analysis used validity and reliability tests, descriptive statistical analysis, and N-Gain Hake tests. The results show that web-based learning media is in the very valid category with a percentage of media expert assessment of 93.5% and material expert of 95%. The level of practicality of media is also in the category of very practical based on the aspects of ease of use, appearance, technical quality, and usefulness. In addition, the results of the effectiveness test showed a significant increase in learning outcomes in the experimental group compared to the control group with a significance value of 0.000 < 0.05 and supported by an N-Gain value which showed the effectiveness of media in improving student understanding. Thus, the web-based learning media developed is declared valid, practical, and effective so that it is suitable for use as a learning innovation in higher education.